2007
DOI: 10.3748/wjg.v13.i2.280
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour intra-arterial infusion of 5-fluorouracil, cisplatin, and leucovorin is more effective than 6-hour infusion for advanced hepatocellular carcinoma

Abstract: AIM:To evaluate the time dependence of intra-arterial 5-fluorouracil (5-FU) therapy for advanced hepatocellular carcinoma (aHCC). METHODS:Thirty-seven adult Japanese patients who had aHCC and liver cirrhosis were treated with combined intra-arterial 5-FU, cisplatin (CDDP), and leucovorin (LV). The Japan Integrated Staging score (JIS score) of each patient was 3 or more. The patients were divided into two groups, after which the 15 patients in group S were treated with 6-h infusion chemotherapy (LV at 12 mg/h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Furthermore, the clinical response completely reflected the survival benefits, as shown in figures 1 and 2. There are several other reports about the possibilities as a treatment for advanced HCC with PVTT, such as intra-arterial infusion chemotherapy with 5-FU and CDDP [27,28,29] or transarterial chemoembolization [30]. A certain level of antitumor effect has been shown in 5-FU and CDDP intra-arterial chemotherapy for the lower stage of HCC patients, but not just for PVTT; antitumor effect for the HCC partially including PVTT patients were not significant compared to IFN-α/5-FU combined treatment in terms of median survival time, response rate and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the clinical response completely reflected the survival benefits, as shown in figures 1 and 2. There are several other reports about the possibilities as a treatment for advanced HCC with PVTT, such as intra-arterial infusion chemotherapy with 5-FU and CDDP [27,28,29] or transarterial chemoembolization [30]. A certain level of antitumor effect has been shown in 5-FU and CDDP intra-arterial chemotherapy for the lower stage of HCC patients, but not just for PVTT; antitumor effect for the HCC partially including PVTT patients were not significant compared to IFN-α/5-FU combined treatment in terms of median survival time, response rate and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that combined intra-arterial therapy with lowdose 5-FU, CDDP, and leucovorin (LV) prolongs the survival of aHCC patients [9]. Moreover, we have shown that continuous intra-arterial infusion for 24 h is more effective than infusion for 6 h in patients with HCV-related LC and aHCC, although 24-h infusion also causes stronger hematologic toxicity [10]. Even when dietary intake is adequate, deficiency of branched-chain amino acids (BCAA) can occur due to enhanced uptake and consumption of these amino acids by skeletal muscle for ammonia metabolism and energy generation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic artery chemotherapy/embolization is the first choice of the unresectable primary hepatic cellular carcinoma (HCC), and plays an important role in the treatment of HCC [1,2] . As to the metastatic liver tumors of colorectal cancer, the artery chemotherapy/ embolization and arterial chemotherapy through percutaneous arterial port-catheter system have already shown its advantage over the systematic chemotherapy [3−5] .…”
Section: Discussionmentioning
confidence: 99%
“…If hepatic artery port-catheter system implantation is considered, it is better to embolize the gastric branches by Microcoils [13,14] to decrease the mucosal injury by chemotherapeutical agents. (2) The bleeding of the distal segment of esophagus and gastric fundus may come from the right gastric artery or accessory left gastric artery,which should not be overlooked in seeking the bleeding site. (3) Both the right gastric artery and the accessory left gastric artery may feed the gastric tumors.…”
Section: Discussionmentioning
confidence: 99%